Classroom management strategies : - Cangelosi, James S. (John Wiley & Sons, Inc., 2014)
In this seventh edition of Classroom Management Strategies: Gaining and Maintaining Students' Cooperation, the practical orientation of prior editions is retained with its pedagogy that leads the pre-service or in-service teacher to discover how to apply research-based strategies in his or her own classroom.